Corruption and Economic Performance: A Causal Analysis of United Nations’ Technical-Political Discourse in the Washington Consensus (1990-2000); [Corrupción y Desempeño Económico: Un Análisis Causal del Discurso Técnico-Político de la Organización de Naciones Unidas Durante el Consenso de Washington (1990-2000)] - Arratia-Sandoval, E (Universidad Adolfo Ibanez, 2023)
Corruption is an important phenomenon for international political economy (IPE), especially in its the causal relation with the State economic performance. Thus, our main objective is to analyse the aforementioned causal relation from United Nations’ (UN) technical-political discourse over the Washington Consensus (WC) under an international relations’ critical realist approach. To achieve this, we use the following instruments: discourse analysis, historical synthesis, process tracing, and counterfactual assessment. The main purpose behind the use of these research techniques is to define, on the one hand, the specific meaning that the UN gives to the corruption-economic performance relation, and, on the other hand, to define the causal mechanism that reveals the aforementioned discourse. Thus, its main feature is the proposition of a qualitative causal mechanism for the economic performance-corruption relation at the global level. Our key research finding is that the evolution of corruption as a special kind of power abuse was solely possible because the roles of the State and the market on economic performance were rethought over the above-mentioned Consensus. © 2023 Universidad Adolfo Ibanez. All rights reserved.